Application of mixed models in the study of the adaptability and stability of short-day and neutral-day strawberry cultivars (Research, Society and Development, 2020)
In strawberry the environmental elements affect the characteristics of productivity and physico-chemical quality of the fruits, when evaluated in different environments. To mitigate the effects of genotype x environment interaction, it is necessary to predict adaptability and stability to identify cultivars with predictable performances between environments. In this context, the objective was to estimate the adaptability and stability of strawberry cultivars using the REML / BLUP procedure. The experiments were carried out in different environments in edaphoclimatic aspects, with 13 strawberry cultivars in a randomized block design, with four replications. As they are characteristics of quantitative origin, the number of commercial fruits (NFC) and mass of commercial fruits (MFC) presented low h2mg, the other characteristics presented values of moderate and high magnitudes for h2mg (0.50 to 0.95). There were changes in the cultivar ordering between environments, reflecting the genotypic correlation between environments, which varied between characteristics. The cultivars highlighted in the ordering through genotypic values were also highlighted by the MHPRVG method. The cultivars Albion, Camarosa and Camino Real were the best for most traits by the MHPRVG method, which reveals good adaptability and stability of these cultivars in relation to the evaluated environments. The mixed model methodology was efficient for selecting superior cultivars in the evaluated environments. Of the tested cultivars Albion, Camarosa and Camino Real were the ones that showed greater adaptability and stability by the MHPRVG method for the environments under study.